MONOCULAR QUADRANTANOPIA CAUSED BY INTRAOCULAR METASTASIS MIMICKING OCULAR TUBERCULOSIS: A NEURO-OPHTHALMOLOGIC DIAGNOSTIC PITFALL - Ervina Rahma Meila Sari; Dinda Husna Azalia Soesetyo; Mahaputri Inas Indrajati; Raden Andi Ario Tedjo; Taufiq Wildan Laksono (Magna Neurologica, 2026)
Background: Monocular quadrantanopia is an uncommon visual field defect that is typically associated with prechiasmal lesions. In tuberculosis-endemic regions, intraocular lesions are frequently attributed to ocular tuberculosis. However, intraocular metastases may present with similar clinical and radiological characteristics, creating significant diagnostic challenges and potentially delaying appropriate management. Case: A 34-year-old man presented with headache and visual field loss in the superior temporal quadrant of the right eye. Neurological examination revealed monocular superior temporal quadrantanopia without additional deficits, while funduscopy showed a superior intraocular lesion. Orbital MRI demonstrated a solid posterior choroidal lesion with mild contrast enhancement, and brain MRI revealed multiple intraaxial supratentorial and infratentorial lesions. Although ocular tuberculosis was initially diagnosed based on epidemiological context and imaging, subsequent investigations excluded tuberculosis. Further systemic evaluation identified a primary lung malignancy, confirming that the intraocular and intracranial lesions represented metastatic disease. Discussion: Quadrantanopia usually results from retrochiasmal lesions, but focal intraocular pathology can mimic neurogenic visual field defects. Distinguishing ocular tuberculosis from intraocular metastasis is difficult because of overlapping clinical and imaging findings. Minimal perilesional edema, absent diffusion restriction, and poor response to antituberculosis therapy should raise suspicion for metastatic disease, underscoring key neuro-ophthalmologic diagnostic pitfalls in infection-endemic settings worldwide regions. Conclusion: Intraocular metastasis should be considered in patients presenting with atypical monocular visual field defects, even when tuberculosis is strongly suspected. Awareness of this diagnostic pitfall is essential to avoid misdiagnosis and delays in appropriate treatment.